Promoting Pre-service Teacher Students’ Learning Engagement: Design-Based Research in a Flipped Classroom - Gu, Jianjun; Tang, Lin; Liu, Xiaohong; Xu, Jinlei (Frontiers in Psychology, 2022)
Students' learning engagement is recognized as one of the main components of effective instruction and a necessary prerequisite for learning, but student engagement in flipped classrooms poses some pedagogical challenges. This study aimed to promote students' learning engagement via the flipped classroom approach. Design-based research (DBR) was adopted in this study to conduct an experiment involving three iterations in a Modern Educational Technology (MET) course in a Chinese university. The participants included 36 second-year pre-service teacher undergraduates. Classroom observations and a learning engagement questionnaire were used to measure the effectiveness of the flipped instruction in terms of students' learning engagement. Data analysis applied descriptive statistics and paired samples t tests. The results showed that after three rounds of iterative experiments, students' learning engagement (behavioral, cognitive, and emotional) significantly improved. Several principles are provided as guidelines for instructors to implement the flipped classroom approach to promote students' learning engagement.